Indonesian Islamic Banking Fintech Model Strategy: ANP Method - R. Donny M. Iskandar; Maryanti, Tatik; Acep R. Jayaprawira; Sari, Siti Nurindah (Pandawan, 2022)
This study aims to analyze the problems, solutions, and strategies of making a fintech model in Indonesian Islamic banking. This study uses non-parametric non-Bayesian qualitative methods for decision-making with a general framework without making assumptions with the Analytical Networking Process (ANP) approach. The researcher selected 11 informants consisting of 2 fintech practitioners, 3 Islamic banking practitioners, one industry 4.0 academic and Islamic sharia banking, one person from the Financial Services Authority, two people from the National Sharia Board, and one from Bank Indonesia. And one person from KNEKS. This study indicates that the problems and solutions for developing the fintech model in Indonesian Islamic banking are divided into internal and external aspects. The main priority of the problem is internal problems, namely the lack of Islamic banking Human Resources who understand IT and Islamic finance. The priority solution is an internal priority, namely a Reliable IT System. The primary importance of the development strategy for forming a fintech model for Islamic banking in Indonesia is the synergy of Islamic banks and Fintech to develop a fintech model for Islamic banks. The theoretical contribution and the results of this study are a novelty in the strategy of Islamic banks in implementing and developing Fintech in Islamic banking. Practical Implication, The managerial implications for Islamic banking practitioners in Indonesia are more focused on procuring a reliable IT system and improving the Human Resources of Islamic banks in mastering IT and Islamic finance.